2021
DOI: 10.1080/20009666.2021.1951943
|View full text |Cite
|
Sign up to set email alerts
|

Health care workers attitudes toward COVID-19 vaccination and the effect on personal and professional life

Abstract: IntroductionWhile the discovery of the Coronavirus disease 2019 (COVID-19) vaccine renewed the hope to restore normal life, the attitude of Health Care Workers (HCWs) towards vaccination and its impact on their life are yet to be evaluated. MethodsWe conducted a cross-sectional study from late January to mid-February at the MedStar Health Hospitals in Baltimore, Maryland. Eligible HCWs completed the questionnaires anonymously. The primary outcomes were attitudes of HCWs towards vaccination and the impact on HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 9 publications
(8 reference statements)
1
10
0
Order By: Relevance
“…This research indicated that vaccinated HCWs had a lower prevalence of psychological outcomes than unvaccinated HCWs against the COVID-19 outbreak in Bangladesh. These findings paralleled a study conducted in the United States among 300 HCWs, which revealed that vaccination against COVID-19 improved HCWs' physical and mental health ( 44 ). Another study conducted in China reported that the COVID-19 vaccine could improve the mental health status of vaccinated individuals ( 45 ).…”
Section: Discussionsupporting
confidence: 78%
“…This research indicated that vaccinated HCWs had a lower prevalence of psychological outcomes than unvaccinated HCWs against the COVID-19 outbreak in Bangladesh. These findings paralleled a study conducted in the United States among 300 HCWs, which revealed that vaccination against COVID-19 improved HCWs' physical and mental health ( 44 ). Another study conducted in China reported that the COVID-19 vaccine could improve the mental health status of vaccinated individuals ( 45 ).…”
Section: Discussionsupporting
confidence: 78%
“…The data in the literature underline the importance of encouraging the implementation of psychological support for staff involved in the health crisis. Nursing home staff are eager to receive psychological care [ 17 , 63 , 64 ]. Nursing home managers could use these results to implement human resources to promote psychological support for staff.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination against COVID-19 may have had an effect on the prevalence of anxiety, depression, and Post-Traumatic Stress disorder in nursing home staff involved in the COVID-19 health crisis. According to Haddaden et al, a COVID-19 vaccination improved healthcare workers’ comfort and anxiety in caring for patients with COVID-19 and other illnesses likely explained by the high efficacy of vaccination in preventing symptomatic infection and critical illness [ 63 ]. The COVID-19 vaccination coverage of the sample was not known.…”
Section: Discussionmentioning
confidence: 99%
“…When interpreting results related to PD, the effect of vaccination on workers should be considered. Vaccination against COVID-19 has been identified to improve the physical and mental wellbeing of workers, by reducing anxiety and improving mood and comfort in job performance ( Haddaden et al, 2021 ). According to the study by Karayürek et al (2021) , vaccination had a positive effect on reducing the fear and anxiety levels of health professionals.…”
Section: Discussionmentioning
confidence: 99%